A Damaged Oxidative Phosphorylation Mechanism Is Involved in the Antifungal Activity of Citral against Penicillium digitatum - OuYang, Qiuli; Tao, Nengguo; Zhang, Miaoling (Frontiers in Microbiology, 2018)
Citral exhibits strong antifungal activity against Penicillium digitatum. In this study, 41 over-expressed and 84 repressed proteins in P. digitatum after 1.0 μL/mL of citral exposure for 30 min were identified by the iTRAQ technique. The proteins were closely related with oxidative phosphorylation, the TCA cycle and RNA transport. The mitochondrial complex I, complex II, complex III, complex IV and complex V, which are involved in oxidative phosphorylation were drastically affected. Among of them, the activities of mitochondrial complex I and complex IV were apparently suppressed, whereas those of mitochondrial complex II, complex III and complex V were significantly induced. Meanwhile, citral apparently triggered a reduction in the intracellular ATP, the mitochondrial membrane potential (MMP) and glutathione content, in contrast to an increase in the glutathione S-transferase activity and the accumulation of reactive oxygen species (ROS). Addition of exogenous cysteine decreased the antifungal activity. In addition, cysteine maintained the basal ROS level, deferred the decrease of MMP and the membrane damage. These results indicate that citral inhibited the growth of P. digitatum by damaging oxidative phosphorylation and cell membranes through the massive accumulation of ROS.